Analysis of Murabahah Risk Management for Profitability Enhancement from a Sharia Management Perspective (Case Study of BPR Syariah Artha Mas Abadi) - Fatikha Rizqya Nur; Lisa Aminatul Mukaromah; Moh. Agus Sifa'; Tri Septiana Wulandari (JOURNAL OF SHARIA ECONOMICS, 2022)
Risk management is a series of measures implemented by Islamic financial organizations to identify, quantify, monitor, and control operational risks. Each bank has a distinct risk management strategy for murabahah funding. This is a sort of qualitative study that employs descriptive data processing. This research intends to investigate the application of risk management by BPR Syariah Artha Mas Abadi, particularly in murabahah financing, which is related to the bank's profitability level and sharia management. The findings of this study indicate that the risk management of murabahah finance at BPR Syariah Artha Mas Abadi, which consists of four steps including identification, measurement, monitoring, and risk control, has been effectively implemented. In order to limit risk, the bank also conducts a 5C study on prospective murabahah financing clients, evaluating their character, capacity, capital, collateral, and economic situation. In accordance with sharia management principles such as fostering justice, openness, kinfolk, and eliminating the element of risywah, implemented risk management also has an influence on raising bank profitability by 80% to 90%.